Figurations : Dossier I - Dossier II. - Musée de Grenoble, Grenoble (Grenoble : Musée de Grenoble, 1978)
di Bartolo, Taddeo ; de Champaigne, Philippe ; Bonnard, Pierre ; de La Villéglé, François ; Wesselmann, Tom ; Bishop, James ; Fromanger, Gérard ; Rancillac, Bernard ; Klasen, Peter ; Monory, Jacques ; Kermarrec, Joël ; Kolar, Jiri
Figurations : Dossier I - Dossier II, Musée de Grenoble, Grenoble, 23 avril - 31 juillet 1978
boek